Maternal, social and health factors influencing admission of newborns to the special newborn care unit at Kakinada, India - Vasireddy, Suhasini; Babu, G. Krishna; Nadipena, Jhansi; Reddy Dalli, Thej Kiran; Aligina, Krishna Kishore; Mahalakshmi, R.; Babji, K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Substantial progress has been made in reducing under five mortality, infant mortality in the last two decades. We need to focus our attention in reducing neonatal mortality. Methods: Setting and design was observational study in SNCU of Government General Hospital, Kakinada. Data collected using semi-structured questionnaire and Hospital Records of mother and newborn. Analysis was done using MS EXCEL2007 and SPSS 20 software. Sample size and time period was a convenient sample of 300 mothers were interviewed from Jan- June, 2018. Results: The mean age of the mothers in the study is 23.39±3.195 years and age at marriage is 19.12±2.29 years. 79% of study population belong to lower social classes. Maternal risk factors-35.6 % are pre-obese or obese and 9.3% underweight, 11.3% had <4 antenatal visits, 87.33% (262) had anemia, 18.33% (55) had PIH. The mean birth weight of newborns was 2601±0.93 grams. 58.3% are preterm and 38.3% (115) low birth weight. 46.33% (139) of newborn admissions were due to birth asphyxia, 27.33% (82) jaundice 9.66% (29) convulsions, 6.66% (20) congenital anomalies, 4% (12) sepsis. Conclusions: Low income, low literacy and less no of antenatal visits showed an association with maternal anemia and LBW (statistically not significant). Upon regression analysis age of mother and gestational period were the only factors with statistical significance.